Pristupi multiomicima u istrazivanju kardiovaskularne bolesti - HE, Guo-Wei (Scripta Medica, 2022)
Cardiovascular diseases remain number 1 killer world-wide. New technologies, particularly the novel approaches at genetics, transcriptomics, proteomics and metabolomics levels have provided new insights into the disease aetiology, pathophysiology and diagnosis, as well as therapeutics from molecular level. These omics by integrating the nuclear, cellular components, proteins, enzymes generate large data sets gather the information with support of organised and systematic computational methods. The integrated analyses may give deeper view on the development, treatment and prevention of the disease. In recentyears, multi-omics technologies have been used in research on cardiovascular diseases including coronary artery disease, heart valve disease and congenital heart disease. These studies help in understanding the aetiology and pathophysiology of the disease and facilitate the precision diagnosis, therapy and prognosis.